2015
DOI: 10.1177/2050640615610266
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, size and shape of colorectal adenomas as determined by a colonoscopist with a high lesion detection rate: Influence of age, sex and colonoscopy indication

Abstract: Background: Increasing attention is focused on polyp-related features that may contribute to the operator-dependent nature of colonoscopy. Few data on polyps are available from high-yield colonoscopies, which may serve as a benchmark for quality control. Objectives: Describe regional distribution, histology, size and shape of polyps, and the influence of patient age and gender, in colonoscopies performed by a colonoscopist with high lesion detection rate. Methods: Analysis of 698 consecutive patients with diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
3
15
1
Order By: Relevance
“…Thus, there may be uncertainties about which polyps are included in the PR concept. For practical purposes, polyps < 5 mm are most likely ignored or biopsied (and up to 80 % of them may not be adenomas 12 ) while polyps ≥ 5 mm are usually suited for true polypectomy by snare and most of these are adenomas. Therefore, if choosing to use PDR-5 mm as a quality indicator until ADR can be made more easily accessible, PR or PDR restricted to polyps ≥ 5 mm may be more valid as a proxy for ADR than a global PDR including diminutive polyps with dominantly non-adenomatous histology.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there may be uncertainties about which polyps are included in the PR concept. For practical purposes, polyps < 5 mm are most likely ignored or biopsied (and up to 80 % of them may not be adenomas 12 ) while polyps ≥ 5 mm are usually suited for true polypectomy by snare and most of these are adenomas. Therefore, if choosing to use PDR-5 mm as a quality indicator until ADR can be made more easily accessible, PR or PDR restricted to polyps ≥ 5 mm may be more valid as a proxy for ADR than a global PDR including diminutive polyps with dominantly non-adenomatous histology.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the incidence of R-sided cancer is increasing and is even more prevalent than L-sided cancer especially in the older age group [ 29 - 31 ]. A recent study also showed that the majority of adenomas were found in the proximal colon for patients beyond age 59 years [ 32 , 33 ]. While the mean age of our patients was 66.1 years, the “proximal shift” of colonic neoplasia may account for the higher risk of metachronous lesions found on surveillance colonoscopy in patients with L-sided tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The same study showed that female patients had a lower prevalence of polyps larger than 9 mm 15 . Other studies have shown an increase in ADR with increasing patient age 15 16 17 and in male as compared to female patients 16 17 18 19 . In a population-based study from the New Hampshire Colonoscopy Registry, the ADR was significantly higher in surveillance colonoscopies (37 %) than screening colonoscopies (25 %; P < 0.001) which is similar to the results of this study 13 .…”
Section: Discussionmentioning
confidence: 82%